Pendampingan Siswa Melalui Penggunaan Math Playground Untuk Melatih Pemahaman Konsep - Hasrita; Nursyam, Aisyah; Aspikal, Aspikal; MS, Andi Trisnowali (Rengganis Jurnal Pengabdian Masyarakat, 2025)
The issue of low conceptual understanding of mathematics, particularly in multiplication, at SD Negeri 02 Mojorejo prompted this community service initiative. The approach used involved the application of digital learning media through the Math Playground website to assist third and fourth-grade students in grasping multiplication concepts in an interactive and engaging manner. The goal of this activity was to enhance students' conceptual understanding of mathematics through guided implementation of Math Playground. The method employed was Participatory Action Research (PAR), which consisted of four stages: identifying the problem, understanding the solution, taking action, and implementing change through evaluation. Results indicated a significant improvement in students' conceptual understanding based on the pretest and posttest results, analyzed using the Wilcoxon Signed Ranks Test, with a significance value (Asymp. Sig. 2-tailed) of 0.046. Additionally, student satisfaction surveys revealed that most students found the platform helpful, motivating, and more engaging for learning mathematics. Thus, this digital media serves as an effective alternative for mathematics instruction at the elementary school level.